STRATEGI KOMUNIKASI PEMASARAN SHOWROOM MOBIL BEKAS DALAM MENINGKATKAN PENJUALAN MELALUI INSTAGRAM AUTOFAME - Gita Adinda Tofan; Silvina Mayasari; Sari Ekowati (CV Edujavare Publishing, 2025)
This research aims to find out the marketing communication strategy applied by Autofame showroom in increasing used car sales through the Instagram social media platform. This research uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Interviews were conducted with the owner of the Autofame showroom and the social media admin who manages the Instagram account. Data analysis techniques used in this research include data reduction, data presentation, and conclusion drawing. The results showed that the Autofame showroom implemented a marketing communication strategy through promotion using public figures or celebrities who visited the showroom and then uploaded their experiences on their respective Instagram accounts and the showroom's official account. In addition, the showroom also actively interacts with potential customers through comments and direct messages on Instagram, and follows the latest automotive trends in an effort to attract the attention of the target market. This strategy proved to be effective in building a positive image and increasing consumer trust in the Autofame showroom, which in turn contributed to increased sales.